The impact of the building envelope on the energy efficiency of residential tall buildings in Saudi Arabia - Ghabra, Noura; Rodrigues, Lucélia Taranto; Oldfield, Philip (Oxford University Press, 2017)
In this paper, the authors explored the hypothesis that the most common approach to improve a building’s energy efficiency in the hot climate of Saudi Arabia, which focuses on engineering parameters, is not sufficient and architectural design parameters should be adopted to reduce cooling loads. In order to investigate this hypothesis, 27 sets of dynamic thermal simulations were compared. The best and worst combinations of glazing ratio, wall and glazing type were identified in order to understand the most influential parameter impacting the cooling energy loads in the building. The findings demonstrated that the reliance on a prescriptive approach for building envelope ‘engineering parameters’ specifications does not achieve the required levels of energy efficiency, and the thoughtful consideration of the ‘design parameters’, such as shading elements, could have a significant impact on cooling energy loads.